"We're all in it together"" The experiences of women aging in place: The case of Searchmont, Ontario - Tessier, Kayla (My University, 2016)
This ethnographic case study of the experiences of older women aging in place in Searchmont, a community with a population of 293 people in northeastern Ontario, has three objectives: 1) to discover the experiences of older women in Searchmont, 2) to explore the connection between women and their community, and 3) to draw conclusions about the structural context of aging in a rural community in northern Ontario. With a growing number of older adults moving into rural communities, or remaining in rural communities into older age, it is a timely exploration. Current policy trends and service restructuring are especially harmful toward vulnerable groups, including older women living outside of the urban context. Cuts to rural services, the privatization of services, and an increased reliance on informal support networks to meet the demands of an aging population create barriers to aging in place. Current trends result in patchwork transit solutions, limited access to information and services, and housing concerns. These factors impact the health and wellbeing of rural-dwelling older women. In addition to large-scale trends, geographic context plays an important role in determining the level of support for older women in rural areas. Aging in place, critical feminist gerontology, and ecological systems theories were used to conduct this case study. The subject of the study includes a history of Searchmont and findings from interviews with five older women living in the community, highlighting the intersection of age, gender, and rural identity. The participants revealed the importance of community fluctuations and meso-level concern for community cohesion into the future. The role of gender in family and community, and level of activity as determined by health were cited as contributors to community sustainability.